The Signifying Animal The Grammar of Language and Experience - Carr, Gerald F.; Rauch, Irmengard (Indiana University Press, 1980)
The boundaries between linguistics and the various humane sciences- philosophy, psychology, anthropology-continue to shrink, and at the same time the two disciplines of linguistics and semiotics are being brought into direct contact with each other. It is the exploration of this interface that concerns Irmengard Rauch in the opening chapter, "What Is Signifying?" The remaining thirteen essays consider all aspects of language as semiotic act in six major topic divisions: definition of language; the pragmatics, semantics, and syntax of the language act; the Peircean categories of Firstness, Secondness, and Thirdness; language in relation to nonverbal communication; the language-likeness in animate existence; and the intersection of linguistics and semiotics. The contributors to this volume are William P. Alston, Raimo Anttila, John N. Deely, William Orr Dingwall, Paul Ekman, Robert B. Lees, David McNeill, Charles E. Osgood, Roland Posner, Joseph Ransdell, Irmengard Rauch, David Savan, and Rulon S. Wells.